Simulated voyages : using simulation technology to train and license mariners (National Academy Press, 1996)
This book assesses the state of practice and use of ship-bridge simulators in the professional development and licensing of deck officers and marine pilots. It focuses on full-mission computer-based simulators and manned models. It analyzes their use in instruction, evaluation and licensing and gives information and practical guidance on the establishment of training and licensing program standards, and on simulator and simulation validation.